The influence of 14CO2 releases from regional nuclear facilities at the Heidelberg 14CO2 sampling site (1986-2014) - Kuderer, Matthias; Hammer, Samuel; Levin, Ingeborg (Atmospheric chemistry and physics, 2018)
Abstract. Atmospheric Δ14CO2 measurements are a well-established tool to estimate the regional fossil-fuel-derived CO2 component. However, emissions from nuclear facilities can significantly alter the regional Δ14CO2 level. In order to accurately quantify the signal originating from fossil CO2 emissions, a correction term for anthropogenic 14CO2 sources has to be determined. In this study, the HYSPLIT atmospheric dispersion model has been applied to calculate this correction for the long-term Δ14CO2 monitoring site in Heidelberg. Wind fields with a spatial resolution of 2.5° × 2.5°, 1° × 1°, and 0.5° × 0.5° show systematic deviations, with coarser resolved wind fields leading to higher mean values for the correction. The finally applied mean Δ14CO2 correction for the period from 1986-2014 is 2.3 ‰ with a standard deviation of 2.1 ‰ and maximum values up to 15.2 ‰. These results are based on the 0.5° × 0.5° wind field simulations in years when these fields were available (2009, 2011-2014), and for the other years they are based on 2.5° × 2.5° wind field simulations, corrected with a factor of 0.43. After operations at the Philippsburg boiling water reactor ceased in 2011, the monthly nuclear correction terms decreased to less than 2 ‰, with a mean value of 0.44 ± 0.32 ‰ from 2012 to 2014.